THE VALIDITY OF TURKEY-LIBYA’S AGREEMENT ON MARITIME BOUNDARIES IN INTERNATIONAL LAW - Yordan Gunawan; Verocha Jayustin Sastra; Adyatma Tsany Prakosa; Mutia Ovitasari; Lathifah Yuli Kurniasih (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2020)
The conflicts between Turkey and Greece have been going on for a long time. Several conflicts caused tension between Turkey and Greece, such as the territory of Aegean, Cyprus, and other problems. The tension increased because the bilateral agreement between Turkey and Libya on the maritime boundaries of the Eastern Mediterranean, which signed in 2019, was opposed by Greece because the Agreement did not take into account the existence of the island which owned by Greece. The Agreement between Turkey and Libya made Greece furious because Greece considered that the action violated Greece’s sovereignty. The research aims to find out further about the validity of the agreement between Turkey and Libya on the maritime boundaries, which threatened Greece’s sovereignty. By using normative legal research, the research emphasizes the bilateral agreement between Turkey and Libya is invalid since it against the international law principles, namely sovereignty of states, good faith, good neighborhood, and Treaty of Amity and Cooperation. The paper will contribute to giving a theoretical understanding regarding aspects that need to be considered, outside the procedural aspects, when a state wants to make an agreement with another state, according to international law.